2021
DOI: 10.1016/j.envexpbot.2021.104387
|View full text |Cite
|
Sign up to set email alerts
|

Volatile organic compound emission in tundra shrubs – Dependence on species characteristics and the near-surface environment

Abstract: Highlights Vapor pressure deficit strongly influenced VOC emission of tundra shrubs. Evergreens had a higher leaf-to-air temperature difference than deciduous shrubs. Leaf traits affected VOC emission of deciduous tundra shrubs. All shrubs had a higher temperature optimum for photosynthesis than expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 86 publications
2
20
0
Order By: Relevance
“…The isoprene emission increased exponentially with temperature but it is hard to state if the optimum temperature was reached in our study. In a subarctic Salix myrsinites, isoprene emission increased exponentially across the temperature range of 10-38 • C without reaching a maximum [71]. According to Niinemets et al [72], the optimum often occurs around 40 • C, suggesting that this could be the same for the varieties in this study.…”
Section: Isoprene Emissions Net Assimilation and Water Use Efficiencysupporting
confidence: 59%
“…The isoprene emission increased exponentially with temperature but it is hard to state if the optimum temperature was reached in our study. In a subarctic Salix myrsinites, isoprene emission increased exponentially across the temperature range of 10-38 • C without reaching a maximum [71]. According to Niinemets et al [72], the optimum often occurs around 40 • C, suggesting that this could be the same for the varieties in this study.…”
Section: Isoprene Emissions Net Assimilation and Water Use Efficiencysupporting
confidence: 59%
“…We ran MEGAN for our tundra sites using the PPFD measured by us in situ. Given the short stature of the tundra vegetation and the great disparity between air and vegetation temperatures found in Arctic ecosystems (16,48,49,54), we forced the model to set the leaf temperature equal to our measured vegetation surface temperature, instead of using leaf temperatures calculated with its leaf energy balance model. In addition, MEGAN's light and temperature activity factors account for the past conditions (using the moving average of the last 24 h and the last 10 d) to model the response to light and temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Now we are pleased to report there has been an upswing in the number of studies on primate olfaction and increasing appreciation of its importance 28,46,47 . These studies have been facilitated in part by improvements in the technology for sampling, storing, and analyzing volatile organic compounds (VOCs) under field conditions 48–50 …”
Section: Overview Of Current Knowledgementioning
confidence: 99%
“…28,46,47 These studies have been facilitated in part by improvements in the technology for sampling, storing, and analyzing volatile organic compounds (VOCs) under field conditions. [48][49][50] For example, Dominy et al reported anecdotal evidence and a personal communication that marmosets scent-mark feeding sites. Recent studies provide direct behavioral evidence of this behavior and report the VOC composition of marmoset scent marks deposited at feeding sites and of dietary exudates.…”
Section: Comparative Sensory Ecologymentioning
confidence: 99%